Separation and recovery of palm mesocarp and nuts using the newly-developed batch drupe dehusker machine - Vincent Eddy, Christine Jamie (2021)
The disproportionate nut-to-fiber ratio in the different breeds of the palm oil fruitlets allows for inadequate screw-pressing and high oil loss to fiber. Overpressing causes nut breakage and mixing of the two different oils together (Crude Palm Oil and Kernel Palm Oil) which affects the oil quality. Manual dehusking of oil palm fruitlets in conducted in research centers using handcrafted knives is very tiring and labor intensive. Due to the restrictions in both of these processes, this study was initiated to simultaneously solve them with the development of a Drupe Dehusker machine to dehusk the fibrous outer layer of a drupe fruitlets from its nut, specifically, the oil palm fruitlets (Elaeis Guineesensisis) to improve mesocarp and kernel recovery. The drum-type batch system’s main mechanism is through the process of molecular dissociation achieved through centrifugal force combined with frictional action between the fruitlets and blades incur in the system. The angles of the blades are 70 degrees and the effective working volume is at ¼ of the total peeling compartment volume. It was found that fruitlets sterilized at 105˚C / 0.121 MPa for 60 minutes is the most optimum condition prior to dehusking of the fruitlets based on the oil quality analysis done based on the Free Fatty Acid, Deterioration of Bleachability Index (DOBI), Carotene content and Moisture content. The structural studies conducted inferred that the heat treatment was definitely found to assist in the structure alteration of the fruitlet. The dehusking efficiency of the Drupe Dehusker machine at 95% is attainable for the dehusking of ideal weight 4 kg load at speed of 25 Hz for the current radius size of the peeling disc at 0.1575 m. Based on the Finite Element Analysis, the machine must be prevented from operating at 32Hz and 43Hz which are same as the natural frequencies to prevent resonance from happening which could lead to machine failure. Economic analysis of the machine inferred that the current machine would generate a net annual profit of RM 91649.89 with Benefit-Cost-Ratio of 5.45, a Return on Investment of 386% with a Pay-Back Period of 0.18 year. Further study could be done in order to obtain the optimum load for the current size of machine and operating disc of radius 0.1575m at the reported speed of 28.85 Hz. Future research could also be conducted to design the system to convert current batch system into continuous system that does not require manual unloading process of the nuts which at current is manually collected after every process.